HEALTH HAZARDS OF COCONUT OIL A MYTH OR REALITY? - B.CHEMPAKAN (International Coconut Community, 1992)
Coconut oil which forms about 4.9 per cent of the world production of oils and fats, assumes much importance among the common vegetable oils in the world. But the alleged atherogenicity of coconut oibdue to its highly saturated nature hinders coconut oil from having a top position in the world market as an edible oil. The recent classification of oils based on the chain length of fatty auds, as MCT and LCT, reveals the neutral effect of coconut oil, which is also supprted by epidemiological observations. Here the possibilities of labelling cocbout oil as an energy giving non‑fattening edible oil is discussed, to dispel the prevailing misconceptions.